MANAJEMEN STRATEGIK BAITUL MAAL WA TAMWIL AL ISHLAH JAMBI: ANALISIS MATRIKS SWOT PERSPEKTIF SYARIAH - Dea Safira; Agustina Mutia; Bilqis Kirana Putih; Musripa; Ambri Riansah; Andrye Afriadi (JSE: Jurnal Sharia Economica, 2026)
This study analyzes the strengths, weaknesses, opportunities, and threats (SWOT) of BMT Al Ishlah Jambi from a sharia perspective. As one of the oldest Islamic microfinance institutions in Jambi City, BMT Al Ishlah has developed strong community trust. This research employs a descriptive qualitative method using in-depth interviews, observation, and documentation. The findings show that the institution’s strengths include the implementation of murabahah and wakalah contracts, selective financing practices that maintain low non-performing financing (NPF), and effective word-of-mouth promotion. Its weaknesses involve limited human resources, low digital technology adoption, and minimal youth participation. Opportunities arise from easier licensing through the OSS system, partnership expansion, and salary deduction programs for teachers and civil servants. Threats include competition from Islamic financial institutions, post-pandemic impacts, and limited Islamic cooperative regulations. Based on these findings, SO, WO, ST, and WT strategies grounded in Islamic principles are formulated to support sustainable and sharia-compliant institutional development.